The Elasticity of Taxable Income in the Presence of Deduction Possibilities - Philipp Doerrenberg; Andreas Peichl; Sebastian Siegloch (Center for Economic Studies and ifo Institute (CESifo), 2015)
Several recent studies show that the elasticity of taxable income (ETI) is not a sufficient statistic for the welfare costs of taxation due to factors such as taxbase shifting. This paper provides an additional argument demonstrating the non-sufficiency of the ETI, namely tax deductions. Building on a theoretical framework which incorporates deductions in a standard optimal-tax model, we show that the ETI is not sufficient for welfare analysis if (i) deductions generate externalities and if (ii) deductions are responsive to tax-rate changes. While the first condition should arguably hold true for the majority of tax deductions, we provide an empirical examination of the second condition. Relying on rich German panel data from administrative tax records, we exploit several tax reforms that were implemented in Germany between 2001 and 2008. Our main estimates indicate an overall ETI between 0.35 and 0.68 and an elasticity of deductions with respect to the net-of-tax rate between -0.3 and -0.9. These results suggest that the ETI is not sufficient to calculate the welfare cost of taxation.
Keywords: H24; H31; 330; elasticity of taxable income; deductions; tax expenditures; sufficient statistic; administrative data; Germany